2023
DOI: 10.1242/dev.202148
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic metabolism during early mammalian embryogenesis

Jing Zhao,
Wenjie Wang,
Ling Zhang
et al.

Abstract: Dynamic metabolism is exhibited by early mammalian embryos to support changing cell fates during development. It is widely acknowledged that metabolic pathways not only satisfy cellular energetic demands, but also play pivotal roles in the process of cell signalling, gene regulation, cell proliferation and differentiation. Recently, various new technological advances have been made in metabolomics and computational analysis, deepening our understanding of the crucial role of dynamic metabolism during early mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 129 publications
0
1
0
Order By: Relevance
“…However, the beneficial effect of lactate addition in embryo development was displayed in 2-cell embryos and 4-cell embryos, but not in blastocysts. One possible speculation is that the embryo metabolic patterns shift gradually from the pyruvate and lactate metabolism to oxidative phosphorylation after densification [ 73 ]. However, more accurate mechanisms require further study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the beneficial effect of lactate addition in embryo development was displayed in 2-cell embryos and 4-cell embryos, but not in blastocysts. One possible speculation is that the embryo metabolic patterns shift gradually from the pyruvate and lactate metabolism to oxidative phosphorylation after densification [ 73 ]. However, more accurate mechanisms require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that for cultivating embryoids beyond the gastrulation stage in vitro, the precise and timely delivery of oxygen, glucose, and the appropriate culture media in specialized incubators is essential [20], there is no evidence that these factors have any direct instructive function for embryonic pattern (basic body plan) development. They should be seen as nutritional needs in a more general sense [37][38][39]. In earlier years, it had indeed been proposed by some researchers that axis development (the embryonic-abembryonic axis, i.e., the precursor for the dorsoventral axis; the anterior-posterior axis), and the laying down of the basic body plan at gastrulation, might be determined by uterine factors (secreted factors or cellular interactions at implantation).…”
Section: A Recent Discussion About Ethical Guidelines and The Term "E...mentioning
confidence: 99%
“…The yolk sac stores a large amount of maternal material accumulated during oogenesis, and serves as a source of nutrients for embryonic development in both viviparous and oviparous vertebrates 1,2 . The metabolism of maternal materials plays an important role in embryonic development 3,4 . Unlike viviparous embryos, oviparous embryos obtain all their nutrients from yolk, highlighting the crucial importance of proper absorption and utilization of yolk nutrients for their development.…”
Section: Introductionmentioning
confidence: 99%